Identifying Bambusa Sp. at TNGGP Resort PTN Selabintana Sukabumi through Mini Research Activities using Project Based Learning - Indri Yani; Suci Pratiwi; Syarifah Zahra; Feizy Fachrunisa Naser; Hesti Nuraeni; Bunda Cintawati (Pedagogia: Jurnal Ilmiah Pendidikan, 2022)
Bamboo is a clear-trunked plant with grass stem type (calamus), which is a stem that is not hard, has real segments, and often hollow. The nature of the surface of the stem is hairy (laevis). The direction of growth is perpendicular (erectus). Bamboo has no branching pattern because it is a monocot. It has books (nodes) and segments (internodes). The cross section of the stem is round (teres) hollow or empty as it is stated by (Yutam Soleh 2013). This study aims to identify Bambusa sp. at Resort PTN Selabintana – Section PTN Region III – Division PTN Region II Sukabumi Gunung Gede Pangrango National Park. The method used is a descriptive exploratory method that describes the identification of Bambusa sp., and a roaming method that is exploring the Resort PTN Selabintana - PTN Section Region III - PTN Division Region II Sukabumi Gunung Gede Pangrango National Park which contains Bambusa sp. The results showed that the species Bambusa sp. found at Resort PTN Selabintana – PTN Section Region III – PTN Division Region III Sukabumi Gunung Gede Pangrango National Park were as many as 5 species, namely Gigantochloa pseudoarundinacea; Dendrocalamus asper; Dinochloa scandes; Bambusa blumeana; Schizostachyum brachycladum.